2014
DOI: 10.1007/s12149-014-0913-y
|View full text |Cite
|
Sign up to set email alerts
|

Grading obstructive lung disease using tomographic pulmonary scintigraphy in patients with chronic obstructive pulmonary disease (COPD) and long-term smokers

Abstract: The severity of chronic obstructive lung disease (COPD) is defined by the degree of flow limitation measured as forced expiratory volume in 1 s, which mainly reflects impairment of large and intermediate airways. However, COPD is primarily a small airways disease. Therefore, better diagnostic tools are needed. Ventilation-Perfusion (V/P) SPECT is a sensitive method to detect obstructive lung changes but criteria for staging airway obstruction are missing.PurposeTo define and validate criteria to stage COPD usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 28 publications
3
31
0
2
Order By: Relevance
“…Advances have improved the diagnostic performances of the test especially in pulmonary embolism diagnosis (23,24) and also in lung functional assessment (25,26). However, the relatively low resolution of SPECT imaging makes accurate delineation and quantification of lung functional volumes difficult (11).…”
Section: Discussionmentioning
confidence: 99%
“…Advances have improved the diagnostic performances of the test especially in pulmonary embolism diagnosis (23,24) and also in lung functional assessment (25,26). However, the relatively low resolution of SPECT imaging makes accurate delineation and quantification of lung functional volumes difficult (11).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decades, the advent of ventilation/perfusion single photon emission computed tomography (V/P SPECT) has improved the diagnostic value of lung imaging by nuclear medicine methods [1,2]. Further benefits are described for the use of hybrid scanners such as PET/CT and SPECT/CT [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Ventilation/perfusion-SPECT (V/P single-photon emission computed tomography) is known as a method for diagnosing pulmonary embolisms, among other conditions. V/P-SPECT was also used in multiple studies to detect and grade pulmonary emphysema [54,55]. As described above, COPD is diagnosed with the aid of spirometry, which reveals obstructive changes in primarily major and intermediate airways through FEV 1 .…”
mentioning
confidence: 99%
“…Because, however, the pathological correlate primarily exhibited by COPD is an obstruction of the minor airways, a better diagnostic method would be desirable. V/P-SPECT can possibly reveal these changes in the minor airways [55]. Individual studies have shown that V/P-SPECT is more sensitive than lung function tests and high-resolution CT [55].…”
mentioning
confidence: 99%
See 1 more Smart Citation